Classical transient receptor potential channel 6 (TRPC6) is essential for hypoxic pulmonary vasoconstriction and alveolar gas exchange - Weissmann, Norbert (National Academy of Sciences, 2006)
Regional alveolar hypoxia causes local vasoconstriction in the lung, shifting blood flow from hypoxic to normoxic areas, thereby maintaining gas exchange. This mechanism is known as hypoxic pulmonary vasoconstriction (HPV). Disturbances in HPV can cause life-threatening hypoxemia whereas chronic hypoxia triggers lung vascular remodeling and pulmonary hypertension. The signaling cascade of this vitally important mechanism is still unresolved. Using transient receptor potential channel 6 (TRPC6)-deficient mice, we show that this channel is a key regulator of acute HPV as this regulatory mechanism was absent in TRPC6(−/−) mice whereas the pulmonary vasoconstrictor response to the thromboxane mimetic U46619 was unchanged. Accordingly, induction of regional hypoventilation resulted in severe arterial hypoxemia in TRPC6(−/−) but not in WT mice. This effect was mirrored by a lack of hypoxia-induced cation influx and currents in smooth-muscle cells from precapillary pulmonary arteries (PASMC) of TRPC6(−/−) mice. In both WT and TRPC6(−/−) PASMC hypoxia caused diacylglycerol (DAG) accumulation. DAG seems to exert its action via TRPC6, as DAG kinase inhibition provoked a cation influx only in WT but not in TRPC6(−/−) PASMC. Notably, chronic hypoxia-induced pulmonary hypertension was independent of TRPC6 activity. We conclude that TRPC6 plays a unique and indispensable role in acute hypoxic pulmonary vasoconstriction. Manipulation of TRPC6 function may thus offer a therapeutic strategy for the control of pulmonary hemodynamics and gas exchange.